Về một ứng dụng của vector time trong các hệ CSDL phân tán - Hải, Nguyễn Nam; Lợi, Phí Mạnh (Journal of Computer Science and Cybernetics, 2016)
For the concurrence control algorithms using timestamp technique in Distributed Database Systems, the technique of generating labels for the events is very important. This paper presents the method of generating label that bases on the technique of Vector time for concurrence control algorithms in Distributed Database Systems. An algorithm basing on  this method has been presented. The evaluation of performance of algorithm is also examined.